DIALECTICAL THEOLOGY AND NON-CHRISTIAN RELIGIONS - Chemparathy, George (Journal of Dharma, 1981)
"Dialectical theology’ ’—also called "crisis theology’ ’—is the name given to a movement which originated within German Protestant theology after the First World War. Its foremost representatives were Karl Barth, Friedrich Gogarten, Eduard Thurneysen, Georg Merz, Emil Brunner and Rudolf Bultmann. This movement arose a as reaction to the liberal Protestant theology developed especially under the influence of Friedrich D. E. Schleiermacher, Albrecht Ritschel, Wilhelm Herrmann and Adolf von Harnack, to mention only the more prominent among its representatives. Under this movement of liberal theology could also be classed a certain relativistic conception of Christianity among the religions proposed by the followers of the school of historv of religions. Perhaps the most important philosopher of this school was Ernst Troeltsch (1865-1923) who, in his celebrated book, Die Absolutheit des Christentums und die Religionsgeschichte (TuebingenLeipzig, 1902 1), challenged the prevalent theological view of Christianity as absolute religion. Being a historical phenomenon, Christianity is conditioned, in his view, by the historical situations and environments in which it found itself, and consequently it cannot be considered as absolute. Christianity is indeed ’ •the loftiest and most spiritual revelation we know at all" and it can be said to be the culminating point of all religions hitherto, but it cannot be proved with certainty that it should remain as the last culminating point.